FAKTOR-FAKTOR PENYEBAB DAN DAMPAK SOSIAL PENGGUNAAN NARKOTIKA PADA REMAJA - Kadek Erika Mulyasih (SOKO GURU: Jurnal Ilmu Pendidikan, 2022)
The use of narcotics is a big concern for all governments, from the central government to the regions. This is done because narcotics abuse continues to grow every year from adults to children, from officials, celebrities and even students. Many things cause it to happen starting from Individual factors, Environmental Factors and Socio-Cultural Factors. In this study, the focus of the research is on what factors cause and the impact of narcotics use on students. The research method in this paper uses a qualitative method with the type of research using a case study that will examine more deeply the causes and effects of narcotics abuse on students. The sample in this study were 3 teenager in Bali City. Data collection was carried out by in-depth interviews of the subjects by telephone. The data obtained, analyzed with data aggregation. The results based on research found that the factors causing narcotics abuse are divided into 2 outlines, namely internal factors and external factors. Internal factors include curiosity, want to follow trends or styles, want to be accepted in the community, as an escape from the pressures of life and an unstable and easily influenced personality while external factors are social environment and family environmental factors while the impact is based on the three informants (KS, MER and DT) there are 4 namely physical, psychological, social and spiritual impacts